Exploring the Variation of Urbach Energies Between Anatase and Rutile Phases of TiO2 Nanoparticles in Polymer-Based Hybrid Composites - L. Jawad , Rasheed; S. Abbas, Raghad (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Titanium dioxide (TiO2) nanoparticles were combined with a mixture of polymers: polyvinyl alcohol (PVA), polyethylene glycol (PEG), and polyvinylpyrrolidone (PVP). TiO2 nanoparticles were formed by the sol–gel process, and nanocomposites were prepared with concentrations 1, 5, 10, 15, 20, and 25 wt% of TiO2 nanoparticles after subjecting them to a calcination process at temperatures of about 400 °C and 700 °C, and with polymer blends of different concentrations (PVA various wt%, PEG constant wt%, and PVP constant wt%). A UV–Vis spectrometer was used to determine the optical constants of the prepared samples, namely, the absorption coefficients and Urbach energies. It was observed that the Urbach energies were highest for the samples with calcination temperature 400 °C and 20 wt% TiO2 nanoparticles blended with PVA 65 wt%, PEG 10 wt%, and PVP 5 wt%. The Urbach energy for the PVA–PEG–PVP polymer blend was 0.32 eV. For the anatase phase (calcination at 400 °C), the Urbach energy was in the range of 0.41–5.55 eV for PVA–PEG–PVP–TiO2 nanocomposites, and for the rutile phase (calcination at 700 °C) it was in the range of 0.31–1.94 eV. The findings have important ramifications for applications of these nanocomposites as reusable photocatalysts, by providing a means of extending their useful life.